ChemInform Abstract: Surface Treatment for Conductive 12 CaO·7 Al2O3 Electride Powder by Rapid Thermal Annealing Processing and Its Application to Ammonia Synthesis. Issue 37 (16th September 2014) - Hayashi, Fumitaka; Kitano, Masaaki; Yokoyama, Toshiharu; Hara, Michikazu; Hosono, Hideo
Abstract [Ca24Al28O64] 4+(e‐)4 electride powder with moderate surface area of 9—19 m2/g is synthesized from an 11:14 stoichiometric mixture of Ca(OH)2 and Al(OH)3, which is hydrothermally treated at 150 °C for 5 h.